Civilizations of ancient Iraq - Foster, Benjamin R. 1945-; Foster, Karen Polinger 1950- (Princeton Univ. Press, 2009)
In Civilizations of Ancient Iraq, Benjamin and Karen Foster tell the fascinating story of ancient Mesopotamia from the earliest settlements ten thousand years ago to the Arab conquest in the seventh century. Accessible and concise, this is the most current and authoritative book on the subject. With illustrations of important works of art and architecture in every chapter, the narrative traces the rise and fall of successive civilizations and peoples in Iraq over the course of millennia--from the Sumerians, Babylonians, and Assyrians to the Persians, Seleucids, Parthians, and Sassanians.Ancient Iraq was home to remarkable achievements. One of the birthplaces of civilization, it saw the world's earliest cities and empires, writing and literature, science and mathematics, monumental art, and innumerable other innovations.Civilizations of Ancient Iraqgives special attention to these milestones, as well as to political, social, and economic history. And because archaeology is the source of almost everything we know about ancient Iraq, the book includes an epilogue on the discovery and fate of its antiquities. Compelling and timely,Civilizations of Ancient Iraqis an essential guide to understanding Mesopotamia's central role in the development of human culture.
Keywords: Geschichte Anfänge-630; Irak; Alltag, Brauchtum; Cultuurgeschiedenis; Funde; Geschichte; Kulturgeschichte; Oudheid; Civilization, Assyro-Babylonian; Assyria -- Antiquities; Babylonia -- Antiquities; Babylonia -- Social life and customs; Iraq -- History -- To 634; Mesopotamien